Estrutura trófica de peixes exploradores de fundo na planície de inundação do alto rio Paraná : fontes de energia e posição trófica. - Lopes, Célia de Almeida (2007)
This work purposed to determine if bottom-feeding fish use different energy sources and if spatial variability occurred in their diets in the Upper Paraná River floodplain. In order to achieve this, it was investigated carbon isotopic composition (δ13C) and the composition and contribution of their alimentary sources during rain periods. Selected species belonged to different trophic categories, for instance, Apareiodon affinis, Cyphocharax nagelii, Prochilodus lineatus, Steindachnerina brevipinna and S. insculpta are iliophagous; Loricariichthys platymetopon and Liposarcus anisitsi are detritivorous; Satanoperca pappaterra and Hoplosternum littorale are benthophagous. Isotopic values of COP varied spatially, in contrast of the isotopic values of other sources. Isotopic variability was verified among the species of fish from all investigated trophic categories. Significant spatial difference was observed among the representatives of each trophic category, which presented the greatest spatial distributions. The highest participation of C4 and C3 macrophytes in the isotopic composition of fish occurred in the Paraná River and Ressaco do Pau Véio Lagoon, respectively. For other locals, riparian vegetation and phytoplankton contributed the most. The COP presented high contribution for fish, principally, among iliophagous from Paraná and Ivinheima rivers and Ressaco do Pau Véio e Maria Luiza lagoons. The highest contributions of zoobentos occurred in the Baía River disconnected lagoons, especially, among the benthophagous and detritivorous. Thus, the spatial and taxonomic variabilities evidenced the necessity of performing specific/local ecological studies for the understanding of energy flow, mainly in food webs from neotropical floodplain.